2018
DOI: 10.1186/s13017-018-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Should ambulatory appendectomy become the standard treatment for acute appendicitis?

Abstract: BackgroundAppendectomy is increasingly performed as a ‘short stay’ or ‘ambulatory’ procedure, yet there is no consensus for selection of patients with acute appendicitis for ambulatory surgery (AS). We aimed to compare characteristics and outcomes of complicated and uncomplicated appendectomies performed in ambulatory vs. conventional settings, and to determine factors associated with unexpected re-consultations and re-hospitalizations.MethodsThe authors reviewed a consecutive series of 185 laparoscopic append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…Appendicitis in this study population was predominantly an adult disease, where no infant, below five years of age, had an appendectomy. This is in keeping with other studies, suggesting that appendicitis is currently increasing in older age groups and it is no longer just in the realm of paediatric surgeons [ 18 , 19 , 20 ]. It reflects the increasing complexity of adult emergency general surgery decision making and the need for quality and performance [ 13 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Appendicitis in this study population was predominantly an adult disease, where no infant, below five years of age, had an appendectomy. This is in keeping with other studies, suggesting that appendicitis is currently increasing in older age groups and it is no longer just in the realm of paediatric surgeons [ 18 , 19 , 20 ]. It reflects the increasing complexity of adult emergency general surgery decision making and the need for quality and performance [ 13 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of appendicitis in the current study occurred higher among young age groups 20–39 years old 48.0% among males and 43.4% among females and this confirmative with previous report study in United States age groups 18–39 years old by 55.4%. [ 21 ] The present study revealed that the prevalence of appendicitis is higher among males (62.6%) compared to the females (37.6%), this is consistent with the previously reported appendicitis prevalence by gender in France[ 22 ] (males 57.8% vs females 42.2%). Moreover, the increased risk of male versus female and age <50 versus age > is in line with the recent literature[ 23 ] and confirming our study.…”
Section: Discussionsupporting
confidence: 92%
“…Median LOS in the entire cohort in our study was 3 days, similar to previous reports 19,26 . On the other hand, there are studies reporting LA in uncomplicated acute appendicitis in an ambulatory setting 2730 . Therefore, to confirm the real prolonged LOS we used 2*75 IQR of the entire cohort (8 days).…”
Section: Discussionmentioning
confidence: 99%